Tinjauan Ilmiah terhadap Sel Punca Dewasa: Peran Terapeutik, Keamanan, dan Aplikasinya dalam Penyakit Degeneratif - Novita Trianah; Saptiawati Saptiawati; Ceni Liswati; Rina Hidayati Pratiwi (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
Stem cells are unspecialized cells with the ability to self-renew over long periods of time without undergoing significant changes in their basic properties. The discovery of adult stem cells has revolutionized therapeutic and regenerative medicine and led to the development of new therapies for previously untreatable terminal conditions. Hematopoietic stem cell transplantation was the first example of successful stem cell therapy and has been widely used in the treatment of a variety of diseases, including leukemia, adult T-cell lymphoma, and multiple myeloma. Meanwhile, autologous mesenchymal stem cell transplantation is increasingly being used to repair mesenchymal tissues and other organs such as the lung and heart, and has shown promise in the treatment of stroke, multiple sclerosis, and diabetes. Interest in the therapeutic potential of other adult stem cells including neural, mammary, intestinal, inner ear, and testicular stem cells is also growing. The discovery of induced pluripotent stem cells has opened new insights into the epigenetic mechanisms underlying pluripotency and carcinogenesis. This study employed a qualitative approach with a literature review method, aiming to conduct an in-depth review of the scientific literature related to the development of stem cell therapy and its epigenetic implications. Through a systematic analysis of various academic sources, this study seeks to formulate a comprehensive conceptual understanding and identify future directions for safer and more targeted stem cell therapy development.